Konsep Manajemen Kepemimpinan Kepala Sekolah Perempuan di Kabupaten Sumenep - Junaidi, Junaidi; Hariyati, Nunuk; Rahem, Zaitur (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
The principal is the most important role in advancing an educational institution. Visionary leadership patterns such as the two institutions in Sumenep district are one of the benchmarks for the development and progress of the world of education in this era. The involvement of female school principals signals the demise of the perception in society that gender issues are no longer relevant. With a qualitative approach, this article highlights the reality of women's leadership in Sumenep district in carrying out leadership duties and is able to create a more lively leadership atmosphere in educational institutions. The findings from this research are that the leadership of a number of female school principals in Sumenep district was able to improve the quality of education